Meningkatkan Kualitas Pendidikan Anak Usia Dini melalui Program Bimbingan di Desa Batu Melenggang Kecamatan Hinai - Zainal Abidin (peduli riset dan pengabdian masyarakat, 2025)
This Community Service Program (PKM) aims to improve the quality of early childhood education through an educational guidance program in Batu Melenggang Village, Hinai District. The problems addressed include the low level of parental assistance in children’s learning at home, limited parental understanding of early childhood education, and the lack of structured educational development activities within the community. The program was implemented using a participatory approach, including early childhood education socialization, learning guidance, character development, parental assistance, and play-based educational activities. The results of the program indicate an increase in children’s learning interest, development of cognitive, social, emotional, and moral aspects, as well as increased parental awareness of the importance of early childhood education. This program demonstrates that community-based educational guidance can serve as an effective strategy for sustainably improving the quality of early childhood education.